An In Vitro Biomechanical Study Evaluating Cervical Extension Plates for Stabilizing Degenerated Adjacent Levels. Issue 1 (February 2017) - Majid, Kamran; Moldavsky, Mark; Khalil, Saif; Gudipally, Manasa
Abstract : Study Design: To evaluate the biomechanical stability of 2 extender plates in a human cervical cadaveric model. Objectives: To evaluate 2 extender plates, placed adjacent to initially implanted plates and to compare their biomechanical stability with traditional techniques. Summary of Background Data: Traditionally, adjacent level degeneration is surgically treated by removing the previously implanted plate and extending the instrumentation to the new degenerated level. The exposure needed to remove the previously implanted plate may be extensive. To overcome these complications, cervical extension plates, which add-on to the initially implanted plate, were developed. Materials and Methods: Fourteen fresh-frozen human cadaver cervical spines (C2–C7) were divided into 2 groups of 7 for a series of constructs to be tested. In group 1, an extender plate, which attaches to its own primary plate, was tested. In group 2, a universal extender plate, which can be placed adjacent to any previously implanted plate, was tested. The specimens prepared were mounted on a 6-degree-of-freedom spine simulator and were sequentially tested in the following order: (1) intact; (2) single-level plate; (3) single-level plate with extender plates; and (4) 2-level plate. An unconstrained pure moment of ±1.5 N m was used in flexion-extension, lateral bending, and axial rotation. Results: All instrumented constructs significantly reduced the range of motion compared with the intact condition. In both the groups, single-level plates with adjacent extender plates demonstrated stability comparable to their respective 2-level plates in all loading modes. Conclusions: Extender plates give surgeons the opportunity to treat adjacent levels without removing the primary implants, which may reduce the overall risk of damage to vital neurovascular structures. From this cadaveric biomechanical model, both types of extender plates prove to be viable options for treating adjacent level degeneration.